2010
DOI: 10.1111/j.1365-2036.2010.04383.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Rome II paediatric criteria on the appropriateness of the upper and lower gastrointestinal endoscopy in children

Abstract: SUMMARY BackgroundThe demand for paediatric gastrointestinal (GI) endoscopy has increased, resulting in a significant rise of overall costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 34 publications
3
23
0
1
Order By: Relevance
“…Among the children undergoing colonoscopy, 43% were subsequently diagnosed with IBD, whereas 52% had normal macroscopic and histological findings. Miele et al [17] report similar findings; they performed a retrospective comparison of the indications and findings of endoscopic procedures before and after strict application of the Rome II criteria for functional GI disorders. They demonstrated an overall increase in colonoscopies performed for IBD (22.9 vs. 63.9%), but also a significant decrease in negative colonoscopies (58.5 vs. 28.7%) [17].…”
Section: Discussionmentioning
confidence: 57%
“…Among the children undergoing colonoscopy, 43% were subsequently diagnosed with IBD, whereas 52% had normal macroscopic and histological findings. Miele et al [17] report similar findings; they performed a retrospective comparison of the indications and findings of endoscopic procedures before and after strict application of the Rome II criteria for functional GI disorders. They demonstrated an overall increase in colonoscopies performed for IBD (22.9 vs. 63.9%), but also a significant decrease in negative colonoscopies (58.5 vs. 28.7%) [17].…”
Section: Discussionmentioning
confidence: 57%
“…Except in one Malaysian study where the inappropriateness was only 0.3%, the remaining studies in children have shown an inappropriateness of 14.3%-26%. [10][11][12][13] The reason may be that the Malaysian study was exclusively screened by gastroenterologists and the procedures were done in a pediatric unit. The other reason may be that this study was done after the ASGE/NASPGHAN guidelines got published, although one study did not find any difference before and after the publishing of these guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…17 Almost similar rates of positive endoscopic findings have been seen in most of the adult and pediatric studies. 10,12,17,19,20 In a small study from Nigeria where 59 children underwent both upper and lower gastrointestinal endoscopy by adult gastroenterologists, a positive diagnostic yield of 89.8% was found without any complications. 21 Adverse events were observed in only 7.3% of patients and all the adverse events were minor and did not increase morbidity or mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that three of the eight alarm symptoms we explored, namely heredity, defecation at night and bloody stools, were significantly more common in OGID than in FGID. Previous studies on paediatric alarm symptoms have been contradictory (), and the 2005 technical report from North American Society for Pediatric Gastroenterology, Hepatology and Nutrition rated alarm signs as evidence quality D .…”
Section: Discussionmentioning
confidence: 99%